Knowledge discovery through composited visualization, navigation and retrieval - Lim, Wei-Ching; Lee, Chien-Sing (Springer Berlin Heidelberg, 2005)
In large databases, many problems occur when visualizing, navigating and retrieving information from databases. Ontologies help in adding semantics and context to the resources in databases. Hence, this paper presents the OntoVis, an ontological authoring and visualization tool, which emphasizes on the clustering of concepts in Formal Concept Analysis (FCA). The composited visualization, navigation and retrieval of resources will be presented in this paper.